3(c+4)=2c+17

Simple and best practice solution for 3(c+4)=2c+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(c+4)=2c+17 equation:


Simplifying
3(c + 4) = 2c + 17

Reorder the terms:
3(4 + c) = 2c + 17
(4 * 3 + c * 3) = 2c + 17
(12 + 3c) = 2c + 17

Reorder the terms:
12 + 3c = 17 + 2c

Solving
12 + 3c = 17 + 2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-2c' to each side of the equation.
12 + 3c + -2c = 17 + 2c + -2c

Combine like terms: 3c + -2c = 1c
12 + 1c = 17 + 2c + -2c

Combine like terms: 2c + -2c = 0
12 + 1c = 17 + 0
12 + 1c = 17

Add '-12' to each side of the equation.
12 + -12 + 1c = 17 + -12

Combine like terms: 12 + -12 = 0
0 + 1c = 17 + -12
1c = 17 + -12

Combine like terms: 17 + -12 = 5
1c = 5

Divide each side by '1'.
c = 5

Simplifying
c = 5

See similar equations:

| ln(5x+9)=6 | | (6x^2+4x+2)+(8x^2+7x)= | | 6x-1/x=0 | | a^2-15+56=o | | -5(4+3y)=-25 | | 5+11x=1+x | | -4a+5-7a=21 | | 4x-6=-2r-18 | | 3x+2(x-16)=8 | | X-2=1/3x | | 33=8(3d-9) | | 8d-12-6d=2 | | 20=4s-6s | | -5h-9-7=-19 | | 9x-36=12x+9 | | 2.5+15+0.5(x-4)=1.2x+2(.9x-6) | | 3(8r+7)=-25 | | 5(3f-8g)+2g= | | 685+85=2 | | 35-4k=-9(8k-5) | | 4y+4-3(-4y-2)=4(y-2) | | -15=-6+9(b-3) | | 4x-71=13x+1-15x | | 4-8(1+6z)=-30 | | 2x(9-6)+32= | | -4(4u-3)+2u=2(u+4) | | 2.5+15+0.5(x-4)=12x+2.0(0.9-6) | | 7c^2+36c+5= | | (8x+4)+(-9x+3)= | | 8x+6x=26 | | 5/9x25/27 | | 8x+40=6x+4 |

Equations solver categories